An overview of molecular basis of iron metabolism regulation and the associated pathologies - Silva, Bruno (2015)
Iron is essential for several vital biological processes. Its deficiency or overload drive to the development of several pathologies. To maintain iron homeostasis, the organism controls the dietary iron absorption by enterocytes, its recycling by macrophages and storage in hepatocytes. These processes are mainly controlled by hepcidin, a liver-derived hormone which synthesis is regulated by iron levels, inflammation, infection, anemia and erythropoiesis. Besides the systemic regulation of iron metabolism mediated by hepcidin, cellular regulatory processes also occur. Cells are able to regulate themselves the expression of the iron metabolism-related genes through different post-transcriptional mechanisms, as the alternative splicing, microRNAs, the IRP/IREs system and the proteolytic cleavage. Whenever those mechanisms are disturbed, due to genetic or environmental factors, iron homeostasis is disrupted and iron related pathologies may arise.